2012
DOI: 10.1080/09291016.2011.605629
|View full text |Cite
|
Sign up to set email alerts
|

Circadian variability and nocturnal dipping pattern in blood pressure in young normotensive subjects

Abstract: Blood pressure variability (BPV) is one of the recognized risk factors for different types of cardiovascular diseases (CVDs). Several physiological, behavioral and ethnic factors are known to modulate blood pressure (BP). Such studies on the population of southeast India are altogether absent. It is worthwhile, therefore, to examine the circadian variability in systolic blood pressure (SBP), diastolic blood pressure (DBP) and heart rate (HR) and nocturnal dipping pattern in BP in apparently healthy human subje… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 43 publications
(54 reference statements)
0
1
0
Order By: Relevance
“…In the present study, 38% of normotensive individuals and 65% of hypertensive were found as non-dippers, whereas, 11% of normotensive and 8% of hypertensive were found as reverse dippers. Nishtha Vaidya et al In their study on circadian variability in young normotensive individuals found 24% of young normotensives as non-dippers [14] . The lesser frequency of non-dipper normal individuals compared to our study may be due to the differences in age range (18-35 years v/s 48.42±14.06).…”
Section: Dipping Statusmentioning
confidence: 97%
“…In the present study, 38% of normotensive individuals and 65% of hypertensive were found as non-dippers, whereas, 11% of normotensive and 8% of hypertensive were found as reverse dippers. Nishtha Vaidya et al In their study on circadian variability in young normotensive individuals found 24% of young normotensives as non-dippers [14] . The lesser frequency of non-dipper normal individuals compared to our study may be due to the differences in age range (18-35 years v/s 48.42±14.06).…”
Section: Dipping Statusmentioning
confidence: 97%